Didactics in social studies for global citizenship education: dimensions and technological contexts - Mellado-Moreno, Pedro C.; Burgos, Carmen (Frontiers in Education, 2025)
The present work presents a conceptual organization scheme based on the latest research in the field of Citizenship Education for Social Studies. In a globalized world, educational systems must equip students with the knowledge, skills, and attitudes to engage proactively in societal issues. Political and social disengagement, particularly among youth experiencing family violence and discrimination, can lead to exclusion and radicalization. School segregation limits the learning of democratic values and harms migrant family participation. Youth tend to favor forms of digital and personal participation over traditional politics. In the digital age, it is crucial to review and adapt civic education, promoting media literacy and the conscious consumption of information. Democratic education should connect knowledge with action to foster active, responsible citizenship, despite the challenge of an academically results-focused environment. To achieve this objective, a literature review was conducted to identify didactics orientations, resulting in a five-dimensional framework: the conceptual dimension advocates for deep and relevant civic education; the participatory dimension encourages active involvement; the prosocial dimension promotes democratic values; the critical dimension develops independent thinking to address inequalities; and the identity dimension strengthens the sense of belonging. These dimensions should be integrated into analog, digital, and immersive contexts to prepare active, critical, and responsible global citizens. This matrix integrates dimensions and contexts to offer better guidance to teachers who impart the subject.